Bloeiende evangelische kerken in Nederland: Een circulation of the saints? - Vermeer, Paul; Scheepers, Peer (Religie & Samenleving, 2017)
This study tries to account for the relative success of six thriving evangelical congregations in the Netherlands. Data gathered among the audiences of these evangelical congregations as well as among a representative sample of the Dutch population are analyzed in view of the following research questions: (1) What was the previous religious affiliation of the current members of these evangelical congregations? and (2) Which decisive factors determined the switch from previous affiliation to current membership of these congregations? Results show that these congregations are populated by a considerable proportion of ‘mainline’ Protestant as well as orthodox Protestant switchers and by an almost equal proportion of previously unaffiliated converts. As regards the second question, results show, that the decision of these switchers and converts to join an evangelical congregation is mainly driven by the religious switching of the partner and to a lesser extent by individual religious concerns.